Prevalence and Socio-Demographic Correlates of Poor Mental Health Among Older Adults in Agricultural Areas of China - Jin, Yu; Zhang, Yun-Shu; Zhang, Qinge; Rao, Wen-Wang; Zhang, Li-Li; Cui, Li-Jun; Li, Jian-Feng; Li, Lin; Ungvari, Gabor S.; Jackson, Todd; Li, Ke-Qing; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Abstract Objective: Poor mental health is associated with impaired social functioning, lower quality of life, and increased risk of suicide and mortality. This study examined the prevalence of poor general mental health among older adults (aged 65 years and above) and its sociodemographic correlates in Hebei province, which is a predominantly agricultural area of China. Methods: This epidemiological survey was conducted from April to August 2016. General mental health status was assessed using the 12-item General Health Questionnaire (GHQ-12). Results: A total of 3,911 participants were included. The prevalence of poor mental health (defined as GHQ-12 total score ≥ 4) was 9.31% [95% confidence interval (CI): 8.4%-10.2%]. Multivariable logistic regression analyses found that female gender [P<0.001, odds ratio (OR)=1.63, 95% CI: 1.29-2.07], lower education level (P=0.048, OR=1.33, 95% CI: 1.00-1.75), lower annual household income (P=0.005, OR=1.72, 95% CI: 1.17-2.51), presence of major medical conditions (P<0.001, OR=2.95, 95% CI: 2.19-3.96) and family history of psychiatric disorders (P<0.001, OR=3.53, 95% CI: 2.02-6.17) were significantly associated with poor mental health. Conclusion: The prevalence of poor mental health among older adults in a predominantly agricultural area was lower than findings from many other countries and areas in China. However, continued surveillance of mental health status among older adults in China is still needed.